2021
DOI: 10.52082/jssm.2021.642
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Digital Media Use and Physical Activity in German Young Adults under the Covid-19 Pandemic - A Cross-Sectional Study

Abstract: Many studies observed a reduction of physical activity (PA) and an increase in digital media use in young adults during the COVID-19 pandemic. However, few studies have been conducted in Europe or looked at changes in the association between both behaviors. Hence, this study aims at investigating the changes in digital media use/social media use and PA as well as in its association among young adults in Germany. Cross-sectional data of 884 German young adults (mean age 22.36 (±1.99), 76% female) collected via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…The decrease in PA level is reported in 13 studies: Franco et al 10 showed a decrease in the proportion of people with low and medium PA in Spain, from 48.8% before to 36% during the pandemic, and similar results are reported in 12 other studies. 7,11,12,14,16,18,20,24,25,28,35,36 Fifteen studies reported a decrease in people’s time doing PA during the COVID-19 pandemic: Bertrand et al 16 reported a decrease in time spent in moderate-vigorous PA per week from 85 min before to 65 min during the pandemic; these results are similar to those reported in other 14 studies. 8,9,15,19,22,26,28-31,33,35,37,38…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The decrease in PA level is reported in 13 studies: Franco et al 10 showed a decrease in the proportion of people with low and medium PA in Spain, from 48.8% before to 36% during the pandemic, and similar results are reported in 12 other studies. 7,11,12,14,16,18,20,24,25,28,35,36 Fifteen studies reported a decrease in people’s time doing PA during the COVID-19 pandemic: Bertrand et al 16 reported a decrease in time spent in moderate-vigorous PA per week from 85 min before to 65 min during the pandemic; these results are similar to those reported in other 14 studies. 8,9,15,19,22,26,28-31,33,35,37,38…”
Section: Resultssupporting
confidence: 76%
“…The characteristics of the articles are presented in Table 1. We included 28 cross-sectional studies 7,8,10,[12][13][14][15][16][17][18][19][20][21][22][23][24][26][27][28][29][30][31][33][34][35][36][37][38] ,4 longitudinal studies. 9,11,25,32 There is one global study, 38 and 2 or more studies covered different countries: 2 from Saudi Arabia., 7,24 5 from Spain 10,25,33,34,36 ,4 from USA 11,14,27,29 ,2 from the UK 17,32 ,3 from Italy, 20,26,37 and 2 from China.…”
Section: Resultsmentioning
confidence: 99%
“…47 Significant associations were found between gaming (b= À0¢21; p = 0¢04), 43 and social media use (b= À0¢06; p = 0¢04), 43 but not smartphone use, 43 or PC/ computer/tablet use. 43,47 Weight gain/BMI. There were two studies, 31,57 each reporting one outcome each, regarding weight gain.…”
Section: Associations Between Screen Time and Multiple Correlatesmentioning
confidence: 97%
“…Associations between overall screen time and physical activity consistently yielded significant results (b= À0¢08; p=<0¢001; One study 30 did not report an effect size, but reported that they had a significant association). 30,43 Conflicting results were found regarding TV use and physical activity, with one study reporting significant associations (b= À0¢15; p=<0¢01), 43 and another showing no significant associations. 47 Significant associations were found between gaming (b= À0¢21; p = 0¢04), 43 and social media use (b= À0¢06; p = 0¢04), 43 but not smartphone use, 43 or PC/ computer/tablet use.…”
Section: Associations Between Screen Time and Multiple Correlatesmentioning
confidence: 99%
See 1 more Smart Citation